2017
DOI: 10.1007/s00441-017-2644-6
|View full text |Cite
|
Sign up to set email alerts
|

Physiological crosstalk between the AC/PKA and PLC/PKC pathways modulates melatonin-mediated, monochromatic-light-induced proliferation of T-lymphocytes in chickens

Abstract: Previous study has demonstrated that melatonin plays a critical role in monochromatic-light-induced lymphocyte proliferation in response to T cell mitogen concanavalin A (ConA). However, its intracellular mechanism is still unclear. In this study, we investigate the intracellular signal pathways of melatonin receptor-mediated T-lymphocyte proliferation in the spleens of chicks exposed to different light wavelengths. Results showed that green light enhanced T-lymphocyte proliferation by 2.46-6.83% and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…The immunohistochemical results showed the expression levels of 3 NR and their locations in the spleens of the broilers. In addition, the expression levels of the 3 melatonin membrane receptors were determined in the spleen ( Guo et al., 2015 ) (data not shown). In the structure of spleen, the white pulp is composed of many lymphocytes, macrophages, dendritic cells and so on, and it is the center of immune activity, whereas the red pulp contains splenic cords and venous sinuses, including red blood cells, reticular fibers, reticular cells, macrophages, and lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The immunohistochemical results showed the expression levels of 3 NR and their locations in the spleens of the broilers. In addition, the expression levels of the 3 melatonin membrane receptors were determined in the spleen ( Guo et al., 2015 ) (data not shown). In the structure of spleen, the white pulp is composed of many lymphocytes, macrophages, dendritic cells and so on, and it is the center of immune activity, whereas the red pulp contains splenic cords and venous sinuses, including red blood cells, reticular fibers, reticular cells, macrophages, and lymphocytes.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are few studies about the light color affecting lymphocyte proliferation. Our previous research found that green light ( GL ) promotes the proliferation of T lymphocytes in the thymus ( Chen et al., 2016 ) or in the spleen ( Guo et al., 2017 ), and it can also promote the proliferation of B lymphocytes in the bursa of Fabricius ( Li et al., 2015 ) of chicks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, melatonin inhibited GnRH secretion by Mel1c in the chick hypothalamus . Melatonin mediated the proliferation of T lymphocytes in GL by Mel1b and Mel1c in the chick spleen . In addition, the roles of the three membrane receptors in the same tissue and organ were different.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, H-89 inhibits the activity of several protein kinases and has various non-PKA-based effects. In addition, melatonin is known to act by modulating signal transduction cascades mediated by various kinases other than PKA, such as MAPK, ERK1/2, and PKC [42][43][44][45]. Melatonin, acting via the MT 1 receptor, and the cAMP-mediated pathways may also elicit signalling responses involving the regulation of chloride, sodium, potassium, or calcium fluxes and of specific ion channels, such as cAMP-mediated phosphorylation of calcium-activated potassium channels (BK Ca ), voltage-dependent calcium channels (VDCC), or inward-rectifier potassium channels (Kir), depending on the cell type [2,46].…”
Section: Discussionmentioning
confidence: 99%